Evaluation of Nephrotoxic Properties of Favipiravir Using the RPTEC cell model - V. A. Evteev; I. S. Semenova; N. D. Bunyatyan; A. B. Prokofiev (Ministry of Health of the Russian Federation, Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products», 2023)
Scientific relevance. Favipiravir is an antiviral RNA polymerase inhibitor used to treat COVID-19. An adverse drug reaction associated with the use of favipiravir is renal disorder.Aim. This study aimed to investigate favipiravir nephrotoxicity by assessing its effects on the integrity of a monolayer formed by renal proximal tubular epithelial cells (RPTECs).Materials and methods. This study focused on an RPTEC monolayer culture that was seeded at a density of 6×104 cells/cm2 on plates with membrane inserts with 0.4 μm pores. Favipiravir was added to the plate wells at a concentration of 5, 10, or 15 μg/mL. The nephrotoxicity evaluation relied on measuring the transepithelial electrical resistance (TEER) of the RPTEC monolayer. A TEER value of 120-140 Ω×cm2 was considered an indication of nephrotoxicity.Results. RPTEC incubation with favipiravir led to a dose-dependent decrease in the TEER values. However, the TEER values after 6 days of incubation ranged within 250-280 Ω×cm2 and were above the critical thresholdof 120-140 Ω×cm2.Conclusions. The results of this study indicate that favipiravir has no pronounced effect on the TEER of the RPTEC monolayer.